Bimetallic Dendrimer-encapsulated Nanoparticle Catalysts. (2nd July 2016) - Wang, Hui; Rempel, Garry L.
ABSTRACT: Bimetallic dendrimer-encapsulated nanoparticles (DENs) have been receiving a significant amount of attention due to their promising properties, unique characteristics, and novel applications in catalysis and other advanced "nano-" science and technology areas. Bimetallic DENs catalysts, as reviewed here, have shown a higher catalytic activity than the monometallic DENs in various catalytic systems. In this review, a general background for the dendrimer is first presented, which is then followed by an introduction of two major routes that are most often adopted in the preparation of dendrimers: divergent method and convergent method. Then, recent research advances in the synthesis, characterization, and catalytic applications of bimetallic DENs are summarized and highlighted in this article. A conclusion is then provided.